2018
DOI: 10.4172/2155-9600.1000728
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Toxic Heavy Metals in Fish after Feeding with Synthetic Feed: A Potential Health Risk in Bangladesh

Abstract: This present research was conducted to assess the bioaccumulation of toxic heavy metals in fish before and after six months feeding with synthetic feed. Here in concentrations of eight toxic heavy metals such as chromium (Cr), copper (Cu), cadmium (Cd), lead (Pb), nickel (Ni), zinc (Zn), iron (Fe) and manganese (Mn) were determined by atomic absorption spectrophotometric (AAS) method. Before feeding, the concentrations in fish were found to be 19.5 ppb, 61.8, 30.5, 35.3, 123.3, 121.9, 197.7 and 543.2 ppb, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Mn concentrations in water samples complied with DWAF [ 37 ] permissible limit of 100 μg/l ( Table 5 ). The Fish feed analysed by Mannan et al [ 98 ] recorded 0.520 mg/kg of Mn concentration which was below the levels from this study (125.91 and 122.58 mg/kg) ( Table 6 ). Mn concentrations in fish feed were above the recommended limit of 100 mg/kg by EC [ 67 ].…”
Section: Resultscontrasting
confidence: 79%
“…Mn concentrations in water samples complied with DWAF [ 37 ] permissible limit of 100 μg/l ( Table 5 ). The Fish feed analysed by Mannan et al [ 98 ] recorded 0.520 mg/kg of Mn concentration which was below the levels from this study (125.91 and 122.58 mg/kg) ( Table 6 ). Mn concentrations in fish feed were above the recommended limit of 100 mg/kg by EC [ 67 ].…”
Section: Resultscontrasting
confidence: 79%
“…Cr exists in various oxidation states ranging from [7–9] including Cr (IV) which is harmful among them at all. The typical reason is its availability in aquatic medium that it readily obtained by body fluids and tissues (Mannan et al, 2018). Research indicated that organic form of Cr might have shown specific effects on bioactivity of insulin, metabolic rates and inflow of blood glucose, because the alterations induced by organic Cr in morphometric parameters of fish shown signs of positive effects (as given in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, tilapia farmers predominantly used commercial brand floating and sinking feed throughout the production cycle. The feed ingredients and feeds purchased from local markets vary in quality, which could be a potential source of contamination [ 51 ].…”
Section: Discussionmentioning
confidence: 99%